2009
DOI: 10.3748/wjg.15.3504
|View full text |Cite
|
Sign up to set email alerts
|

Perianal disease, small bowel disease, smoking, prior steroid or early azathioprine/biological therapy are predictors of disease behavior change in patients with Crohn’s disease

Abstract: Our data suggest that perianal disease, small bowel disease, smoking, prior steroid use, early AZA or AZA/biological therapy are all predictors of disease behavior change in CD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
4
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 30 publications
5
66
4
7
Order By: Relevance
“…The authors found that over 10 years, 45.9% of patients had a change in disease behavior; the most significant changes were from B1 to B2 or B3 behavior (15) . Another recent study considering 340 well-characterized CD patients showed that perianal disease, disease location, and smoking are some independent predictors of disease behavior change (13) . In the present study the changing of disease behavior over time was not assessed; on the other hand, patients were grouped according to disease duration; the results showed that patients with higher disease duration (>10 years) had lesser rates of B1 behavior and higher rates of B2 and B3 behavior, when compared to those with lesser disease duration (<10 years).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that over 10 years, 45.9% of patients had a change in disease behavior; the most significant changes were from B1 to B2 or B3 behavior (15) . Another recent study considering 340 well-characterized CD patients showed that perianal disease, disease location, and smoking are some independent predictors of disease behavior change (13) . In the present study the changing of disease behavior over time was not assessed; on the other hand, patients were grouped according to disease duration; the results showed that patients with higher disease duration (>10 years) had lesser rates of B1 behavior and higher rates of B2 and B3 behavior, when compared to those with lesser disease duration (<10 years).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a significant emphasis was placed on early patient stratification based upon the identifi cation of predictive factors [7] . Phenotypic classification of Crohn's disease plays an important role in deter mining treatment methodology, as it generally assists in predicting the likely clinical course [8,9] . The complex evaluation of clinical presentation, endoscopic findings, fecal, serological, and routine laboratory tests as well as early treatment factors -is recommended.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8]18 Smoking has also been associated with the development and progression of CD, 6,8,[12][13][14]18 increasing the risk for IBD-related surgery. Similarly, perianal disease is associated with an increased risk of progressive complicated CD [8][9][10][11] and resectional surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics and outcomes may inform the clinician as to the therapeutic strategy to adopt, for example early aggressive therapy for those patients who are most likely to progress to surgery. 2,3 A range of factors have been associated with an increased risk of complicated (stricturing and penetrating) CD behaviour including the specific NOD2 genotypes [4][5][6] having had perianal disease [8][9][10][11] and cigarette smoking. 1,6,8,[12][13][14] Complicated disease is strongly associated with a requirement for surgery 15 ; therefore, knowledge of such genetic, environmental and clinical predictors may guide clinicians in developing a personalised approach for individual patients.…”
Section: Introductionmentioning
confidence: 99%